2021
DOI: 10.3389/froh.2021.685236
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Stem Cells: Therapeutic Implications and Challenges

Abstract: Head and neck squamous cell carcinoma (HNSCC) is currently one of the 10 most common malignancies worldwide, characterized by a biologically highly diverse group of tumors with non-specific biomarkers and poor prognosis. The incidence rate of HNSCC varies widely throughout the world, with an evident prevalence in developing countries such as those in Southeast Asia and Southern Africa. Tumor relapse and metastasis following traditional treatment remain major clinical problems in oral cancer management. Current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 209 publications
(235 reference statements)
0
27
0
3
Order By: Relevance
“…Previous studies have suggested that cancers are organized as a cellular hierarchy of various populations of cancer cells, and the hierarchy is maintained by a small subset of cancer cells, called CSCs [ 33 , 34 ]. CSCs have stemness and are also called cancer-initiating cells [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 ]. CSCs were identified for the first time in 1997 by Bonnet and Dick in a patient with acute myeloid leukemia [ 46 ].…”
Section: Cscs In Osccmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that cancers are organized as a cellular hierarchy of various populations of cancer cells, and the hierarchy is maintained by a small subset of cancer cells, called CSCs [ 33 , 34 ]. CSCs have stemness and are also called cancer-initiating cells [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 ]. CSCs were identified for the first time in 1997 by Bonnet and Dick in a patient with acute myeloid leukemia [ 46 ].…”
Section: Cscs In Osccmentioning
confidence: 99%
“…CSCs have also been shown to play important roles in the development and progression of OSCC [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. It is reported that only a small percentage of the cell population contributes to the development of OSCC, and this population has properties corresponding to those of CSCs [ 31 , 40 ].…”
Section: Cscs In Osccmentioning
confidence: 99%
See 1 more Smart Citation
“…Through binding interactions of CD44 with its natural ligands, such as hyaluronic acid or other binding partners secreted in the extracellular matrix, a series of signaling cascades in OSCC cells may be activated, leading to the enhanced tumor growth, metastatic ability, and resistance to cancer treatment [ 16 ]. Therefore, targeting CD44 and its signaling pathways that involve in the cancer-promoting activities has emerged as a novel therapeutic potential for OSCC [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most prevalent forms of neck and head malignancies, oral cancer mostly affects the throat, paranasal sinuses, nasopharynx, hypopharynx, salivary glands, and oral cavity. 1 Except for certain regions of France, oral cancer is rare in the industrialized world. However, it is frequent in the developing world, notably in Southeast Asia and Brazil.…”
Section: Introductionmentioning
confidence: 99%